Attenuating effect of taurine on oxidative damage and Nrf2/HO-1 pathway induced by cadmium in testicular cells of embryonic chickens - LIU Mengqi; ZHANG Guanglu; GUO Changquan; YANG Tingyu; MI Yuling (浙江大学学报. 农业与生命科学版, 2018)
To investigate the attenuating effect of taurine on oxidative damage induced by cadmium in testicular cells of embryonic chicken, embryonic testis cells from 18-day-old chickens were cultured in serum-free McCoy’s 5A medium as a model. By cell morphological observation, methyl thiazolyl tetrazolium (MTT) assay, biochemical index determination, 5-bromo-2-deoxyuridine (BrdU) incorporation, TdT-mediated dUTP nick end labeling (TUNEL) method, Western blotting (WB), fluorescence quantitative polymerase chain reaction (PCR) and immunofluorescence staining methods, cell proliferation, mitochondria signal, endoplasmic reticulum stress signal, nuclear factor-erythroid 2 related factor-2 (Nrf2) and hemeoxygenase-1 (HO-1) signaling were studied to reveal its action mechanisms. The results showed that, cadmium resulted in testicular germ cells of embryonic chicken more vulnerable to oxidative damage. Compared with the control group, the testicular germ cells treated with cadmium presented condensed nuclei, vacuolated cytoplasm and marginalized chromatin. After cadmium treatment, the number of germ cells and cell vitality of embryonic chicken testes decreased significantly. Hydrogen peroxide, malondialdehyde and reactive oxygen species increased significantly, but superoxide dismutase activity decreased significantly. Cell proliferative ability decreased significantly, while apoptotic cells increased significantly. The expression of endoplasmic reticulum stress related genes (GRP78, XBP-1), and apoptosis-related genes (Cyt C, p53 and caspase 9) mRNA increased significantly. Meanwhile, the expression of Nrf2 and p-Nrf2 proteins and HO-1 mRNA increased significantly (P<0.05). However, simultaneous supplementation with taurine significantly restored the oxidative damage induced by cadmium. The germ cell numbers and cell vitality increased apparently; the antioxidant levels and endoplasmic reticulum stress witnessed a return to normal levels. In addition, the number of cell proliferation increased but apoptotic cells experienced a decline, and Nrf2 expression was restored. Consequently, taurine can relieve reproductive toxicity of cadmium, not only by restoring the balance of oxidation and anti-oxidation, but also by promoting testicular cell proliferation and inhibiting apoptosis.